Multislice CT angiography in cardiac imaging. Part III: Radiation risk and dose reduction - Sun, Z.; Ng, K.H. (2010)
With the introduction of 64- or more-slice computed tomography (CT) technology, multislice CT angiography has been increasingly used as a non-invasive modality for the diagnosis of coronary artery disease. Despite its potential advantages and promising clinical results, multislice CT angiography suffers from high radiation dose which contributes to radiation-induced malignancy in patients undergoing cardiac CT examinations. This has raised serious concerns in clinical practice. A number of strategies have been recommended and implemented to reduce the radiation dose associated with multislice CT angiography in cardiac imaging. The aim of this review is to present an overview of the various approaches used for radiation dose reduction. Future directions of multislice CT angiography with regard to the judicious use of this promising technique and increased awareness of the radiation risk are highlighted.